Ultimate limit design of composite beams with modular GFRP deck and steel girder. (1st December 2018) - Hou, Jian; Nie, Xin; Zhang, Lei; Huang, Yuan; Bai, Yu
Highlights: Possible failure modes are analyzed for modular GFRP-steel composite beams. Theoretical formulation of bearing capacity is developed for each failure mode. Flexural failure can be the critical mode for bidirectional composite beams. Vertical shear failure can be the critical mode for unidirectional composite beam. Ductile failure can be achieved with ultimate capacity larger than yield load. Abstract: This paper analytically formulates the ultimate capacities for various failure modes of composite beams consisting of a modular fiber reinforced polymer (FRP) web-flange sandwich deck supported by a steel girder. Pultruded FRP box sections are incorporated between two flat panels to form the web-flange sandwich deck, in which the pultrusion direction of box sections can be either parallel or perpendicular to the span direction. Such a deck can then be assembled via adhesive bonding or blind bolt connections to a supporting steel girder to form a composite beam system. On the basis of theoretical analysis of critical sections for such composite beams at ultimate states, potential failure modes are identified, including flexural failure of the steel girder yielding in tension and GFRP deck failure in compression, vertical shear failure, and horizontal shear failure at adhesive bonding at bolted connections and at webs of FRP box sections. For each failure mode, the corresponding ultimate capacity is analytically formulated; thereby, the critical failure mode and ultimate load capacity can be determined. The developed ultimate limit design approaches are validated by experimental results from the literature for such FRP-steel composite beams.